Cross-Border Commuting between the Czech Republic and Germany - Trager, Johanna; Kalíšková, Klára; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
This diploma thesis focuses on the impact of the first EU eastern enlargement in 2004 and the consequent abolishment of labor market restrictions in 2011 on the number of Czech cross-border commuters to Germany. In the empirical part, a descriptive analy-sis of push and pull factors of cross-border commuting is conducted. No unambiguous evidence was found for changes of the push and pull factors that occurred simultane-ously with the first EU eastern enlargement in 2004 and the abolishment of the labor market restrictions in 2011. Difference-in-Differences analyses between Czech and Austrian cross-border commuters to Germany show a significant impact of the first EU eastern enlargement in 2004 as well as the abolishment of labor market restrictions in 2011 on the number of Czech cross-border commuters. Difference-in-Differences anal-yses between Czech and Polish cross-border commuters to Germany show a signifi-cantly lower impact of the first EU eastern enlargement in 2004 for male Czech cross-border commuters. For female Czech cross-border commuters no significant different impact was obtained. The impact of the abolishment of the labor market restrictions in 2011 was significantly lower for female, but significantly larger for male Czech cross-border commuters compared to Polish cross-border commuters. As a final perspective, a set of expert interviews on the impact of the ongoing COVID-19 pandemic on Czech cross-border commuters to Germany was conducted. A clear emphasis of the inter-viewees was set on the disadvantaged position of Czech cross-border commuters on the German labor market.
Vedoucí práce: Klára Kalíšková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses